Identity, Ethnic Conflict and Communal Conflict in Sub- Saharan Africa - Robert Kłosowicz (Ksiegarnia Akademicka Publishing, 2021)
Ethnic identity is one of the most significant types of identities. Meanwhile, some researchers have recently begun to criticise the term ‘identity’ as being too excessively associated with political ideologies, lacking operational power and being difficult to define precisely. Simultaneously, attention has been drawn to what can be referred to as ‘ethnic revival.’ Ethnic identity is created based on the opposition between what is ‘one’s own’ and what is ‘foreign.’. Even though the category of ‘the Other’ or the ‘foreign’ always appears in the context of identity, it has a special significance in the case of ethnic identity. By such means, the belonging to a particular ethnic group is emphasized, while simultaneously one is cut off from other groups. Conflicts between clans, tribes and ethnic groups have occurred throughout the ages and in all civilisations. There is no single opinion among researchers about how ethnic conflict should be defined. Increasingly, in recent literature of the subject, the distinction between ethnic conflicts and communal conflicts has come to be applied. The article aims to analyse the identity problems expressed in ethnic and communal conflicts in Sub-Saharan Africa. It is based on the critically reviewed literature of the subject, as well as the author’s conclusions from many years of research on the problem of state dysfunctionality, conducted in Sub-Saharan African countries.